Nuclear Scholars Initiative a collection of papers from the 2014 Nuclear Scholars Initiative - a Minot, Sarah e editor (CSIS report, 2015)
"Addressing an increasingly complex array of nuclear weapons challenges in the future will require talented young people with the necessary technical and policy expertise to contribute to sound decisionmaking on nuclear issues over time. To that end, the CSIS Project on Nuclear Issues (PONI) runs a yearly Nuclear Scholars Initiative for graduate students and young professionals. Those accepted into the program are hosted once per month at CSIS in Washington, DC, where they participate in daylong workshops with senior government officials and policy experts. Over the course of the six-month program, scholars are required to prepare a research paper. This volume is a collection of the 2014 papers from the Nuclear Scholars Initiative"--Publisher's web site